Near-Surface Geophysical Characterization of Lithologies in Corfu and Lefkada Towns (Ionian Islands, Greece) - Alexopoulos, John D.; Voulgaris, Nicholas; Dilalos, Spyridon; Gkosios, Vasileios; Giannopoulos, Ioannis-Konstantinos; Mitsika, Georgia S.; Vassilakis, Emmanuel; Sakkas, Vassilis; George Kaviris (Geosciences, 2022)
Lefkada and Corfu old towns are located in the western part of Greece, in the Ionian Sea. Their proximity to the Hellenic subduction zone (HSZ) is the reason for their intense seismicity. The main goal of this study was the estimation of the geotechnical characteristics of the subsurface, with the contribution of applied geophysical techniques. Therefore, seismic refraction tomography (SRT) and multichannel analysis of surface waves (MASW) were applied. A total of thirty-three (33) seismic and geoelectrical profiles were performed in both towns in order to evaluate the geotechnical characteristics of the subsurface formations. Additionally, subsurface resistivity distributions were investigated with the application of electrical resistivity tomography (ERT). Some important elastic moduli were calculated through the combination of estimated seismic wave velocities and laboratory density measurements. The horizontal distribution of seismic velocities and mechanical properties (σ, E, K, G) of Corfu town was illustrated in maps, for the depth of 5 m. The geophysical interpretation also revealed that Lefkada’s subsurface consists of only one compact geological formation, with little or no variation of its geophysical-geotechnical characteristics. Beyond that, the ground type classifications for the two towns were determined according to the European Committee for Standardization Eurocode 8, based on VS30 values.